A Novel Therapeutic Approach Using Mesenchymal Stem Cells to Protect Against Mycobacterium abscessus. (27th March 2016) - Kim, Jong-Seok; Cha, Sang-Ho; Kim, Woo Sik; Han, Seung Jung; Cha, Seung Bin; Kim, Hong Min; Kwon, Kee Woong; Kim, So Jeong; Choi, Hong-Hee; Lee, Jienny; Cho, Sang-Nae; Koh, Won-Jung; et al.
Abstract: Recent studies have demonstrated the therapeutic potential of mesenchymal stem cells (MSCs) for the treatment of acute inflammatory injury and bacterial pneumonia, but their therapeutic applications in mycobacterial infections have not been investigated. In this study, we demonstrated the use of MSCs as a novel therapeutic strategy against Mycobacterium abscessus ( M. abscessus ), which is the most drug-resistant and difficult-to-treat mycobacterial pathogen. The systemic intravenous injection of MSCs not only improved mouse survival but also enhanced bacterial clearance in the lungs and spleen. Additionally, MSCs enhanced IFN-γ, TNF-α, IL-6, MCP-1, nitric oxide (NO) and PGE2 production and facilitated CD4 + /CD8 + T cell, CD11b high macrophage, and monocyte recruitment in the lungs of M. abscessus -infected mice. To precisely elucidate the functions of MSCs in M. abscessus infection, an in vitro macrophage infection system was used. MSCs caused markedly increased NO production via NF-κB activation in M. abscessus -infected macrophages cultured in the presence of IFN-γ. Inhibiting NO or NF-κB signaling using specific inhibitors reduced the antimycobacterial activity of MSCs. Furthermore, the cellular crosstalk between TNF-α released from IFN-γ-stimulated M. abscessus -infected macrophages and PGE2 produced by MSCs was necessary for the mycobacterial-killing activity of the macrophages. Finally, the importance of increased NO production in response to MSC administration was confirmed in the mouse M. abscessus infection model. Our results suggest that MSCs may offer a novel therapeutic strategy for treating this drug-resistant mycobacterial infection by enhancing the bacterial-killing power of macrophages. Abstract : Effects of aminoguanidine on MSC-induced M. abs -R clearance in mice. (A) Schematic diagram of the experimental design. (B) C57BL/6J mice were infected with an aerosolized strain of M. abs -R (1.6 × 10 7 CFUs/mouse), and MSCs (2.5 × 10 5 cells/mouse) were administered by intravenous injection at one day post-infection. Aminoguanidine was administered at a dose of 0.25% ad libitum in the drinking water each day, starting one day post-infection. The data are presented as the means ± SEM of two experiments (**, p < .01 and ***, p < .001). (C) The effects of MSCs on iNOS expression in the lungs of M. abs -R-infected mice. Immunohistochemistry was performed as described in "Materials and Methods" (scale bar = 100 μm). (E) C57BL/6J mice were infected with an aerosolized strain of M. abs -R (1.6 × 10 7 CFUs/mouse), and Cox-2 −/− and iNOS −/− MSCs (2.5 × 10 5 cells/mouse) were administered by intravenous injection at one day post-infection. After 10 day after infection, bacterial CFUs were measured at lung and spleen as described in "Materials and Methods." The results are expressed as the mean estimated CFU ± SEM from the lung samples of five to six mice in two independent experiments. (D) Representative immunohistochemistry staining of iNOS and F4/80 (scale bar = 10 μm).